The University of the 21st Century : Back to the Past - Carbajales, Mariano (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this paper it is proposed to carry out a critical review of the competency-based teaching model - currently in force in most universities around the world, which we have called “professionalizing”, to transform it into a training model based on the original “ liberal arts”, with which the Universities were born and that we have come to call “humanizing” or humanistic.